Topological Spaces with Skorokhod Representation Property - Banakh, T.O.; Bogachev, V.I.; Kolesnikov, A.V. (Український математичний журнал, 2005)
We give a survey of recent results that generalize and develop a classical theorem of Skorokhod on representation of weakly convergent sequences of probability measures by almost everywhere convergent sequences of mappings. Наведено огляд отриманих останнім часом результатів, що узагальнюють класичну теорему Скорохода про зображення слабко збіжної послідовності ймовірнісних мір майже напевно збіжними послідовностями відображень.